PROSPECT OF URANIUM NITRIDE FOR PRESSURIZED WATER REACTOR (PWR) - DEWI SYARIFAH (NIM :20211003) ; Pembimbing Prof. Dr. Eng. Zaki Su'ud, RATNA
A small Pressurized Water Reactors (PWRs) core loaded with uranium nitride fuel (UN) and mixed nitride fuel (UN-PuN), Pa-231 as a material burnable poison, and Americium as a addition of minor actinide has been performed. Pa- 231 known as actinide material, have large capture cross section and capability to convert into fissile material that can decrease excess reactivity. Americium is one of minor actinide which have long half life. The objective of adding americium is to decrease nuclear spent fuel in the world. The neutronic analysis results of infinite cell calculation shows that mixed nitride fuel have k-inf greater than uranium nitride fuel. It caused by the addition of Pu-239 in mixed nitride fuel. In fuel fraction analysis, the optimum fuel fraction are 50% fuel fraction, 20% cladding and 30% moderator. For the addition of Pa-231 and Americium, the lowest excess reactivity for UN when enrichment U-235 9%, Pa-231 1% and Am 1%, the excess reactivity is 7,5%. And for mix nitride fuel, when enrichment U- 235 1%, Pa-231 20% and Am 12%, the excess reactivity is 3,7%. In core configuration, it's better to use heterogeneous than homogeneous core configuration, because the radial power distribution is flatter.